Species identification and genetic diversity of Aedes in Penang (Malaysia) based on Cytochrome Oxidase Subunit I - NUR ZAWANI MUSTAFA KAMAL; MUHAMMAD SIRI DANGNGA; IRMAYANI; Darlina Md. Naim (Nusantara Bioscience, 2020)
Abstract. Kamal MZM, Dangnga MS, Irmayani, Md. Naim D. 2020. Species identification and genetic diversity of Aedes in Penang (Malaysia) based on Cytochrome Oxidase Subunit I. Nusantara Bioscience 12: 6-12. Cases of dengue fever are expanding globally and recently it was identified as being notable in remote/rural regions in South-East Asia in spite of the previous belief that it is outbreak to urban areas, especially in Malaysia. In an effort to constraint, the extent of the virus, the most important thing is to know the distribution of the vector that causes the disease. This research aims to recognize all species of mosquitoes distributed in Penang utilizing DNA barcode method in which the mtDNA cytochrome oxidase subunit 1 (COI) as a gene marker. Approximately 497 larvae of mosquitoes were obtained from four regions in Penang, Malaysia namely Central Seberang Perai, North Seberang Perai, North East, and South West of Penang. All samples were extracted and PCR amplified. Sequences were employed in BLAST of GenBank and aligned with MUSCLE. The ABGD analysis was performed to partition all the samples and substitution saturation analysis was employed in DAMBE. Phylogenetic relationships among nucleotides were reconstructed utilizing Maximum Likelihood (ML) and Neighbor-Joining (NJ) calculated following Kimura 2-parameter. Intra and interspecific genetic variation among population were also conducted based on Tamura-Nei parameter and all analyses were employed in MEGA version 6.0. As a result, COI gene has successfully recognized all larvae obtained in this study. We found a total of six species (including outgroup sequence) as revealed by BLASTn, ABGD and phylogenetic analysis. Genetic distance test has further supported the results. This study revealed that there is no visible population structure and all species have a uniform distribution throughout all sampling locations in Penang. We also found that Ae. albopictus has occupied most areas in Penang, and this includes urban locations, hence, suggest that Ae. albopictus probably succeed Ae. aegypti as the main vector for dengue virus in Penang.